Pengetahuan Remaja Putri tentang Senam Dismenore sebagai Manajemen Nyeri Dismenore di Kediri - Rahmawati, Dian; Agustin, Lia (Jurnal Kesehatan, 2023)
The prevalence of dysmenorrhea in Indonesia is estimated at 55%. For teenage girls or adolescents who need to pay a full attention in learning, dysmenorrhea is a problem that could hinder the learning process. One of the non-pharmacological methods that are effective for dysmenorrhea pain management is dysmenorrhea exercise. The purpose of this study was to find out young women's knowledge about dysmenorrhea exercise as dysmenorrhea pain management in Kediri. This study used a descriptive method with a cross sectional approach. The research population was all adolescent girls of class X IPA SMA Negeri 1 Kandat Kediri Regency as many as 148 people. The sampling technique used was systematic sampling, so that there were 74 female teenagers as the sample. The data was collected using a questionnaire, and then analyzed using percentage. The results showed that 38 respondents (51.4%) had sufficient knowledge, 36 respondents (48.6%) had poor knowledge, and none of the respondents (0%) had good knowledge. It is suggested for young women to be more active in seeking information about dysmenorrhea exercise so that they can reduce the pain caused by the dysmenorrhea.